Analisis Hubungan antara Kemurnian Madu dengan Sifat Fisisnya - Yuant Tiandho; Evi J; Deden Nurdandi; Fenni Vavionita; Eri Gusnia; Umi Awaliyah (Jurnal Riset Fisika Indonesia, 2021)
Public awareness of the benefits of honey has increased the amount of honey consumption. This encourages the circulation of impure honey in the market by irresponsible traders. Therefore, characteristic information of honey is needed as a basis for honey purity testing methods. Physical characteristics analyzed in this study are the refractive index, permittivity, density and color quantization of honey. In general, it can be seen that the higher the concentration of honey, the higher the refractive index and its density and inversely proportional to the permittivity. Color analysis also shows that concentration is inversely proportional to the color intensity level.